2016
DOI: 10.1038/aps.2016.115
|View full text |Cite|
|
Sign up to set email alerts
|

The natural product 4,10-aromadendranediol induces neuritogenesis in neuronal cells in vitro through activation of the ERK pathway

Abstract: Recent studies focus on promoting neurite outgrowth to remodel the central nervous network after brain injury. Currently, however, there are few drugs treating brain diseases in the clinic by enhancing neurite outgrowth. In this study, we established an NGF-induced PC12 differentiation model to screen novel compounds that have the potential to induce neuronal differentiation, and further characterized 4,10-Aromadendranediol (ARDD) isolated from the dried twigs of the Baccharis gaudichaudiana plant, which exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…These ROS are considered to be one of the primary causes for the endothelial cytotoxicity of DL-Hcy. Chang and coauthors showed stimulation of ROS generation by 0.5 and 1.0 mmol/L Hcy in rat vascular smooth muscle cells (VSMC) (27). The same study also demonstrated that CAT activity in VSMC was inhibited by Hcy, which is consistent with the results of our research.…”
Section: Discussionsupporting
confidence: 91%
“…These ROS are considered to be one of the primary causes for the endothelial cytotoxicity of DL-Hcy. Chang and coauthors showed stimulation of ROS generation by 0.5 and 1.0 mmol/L Hcy in rat vascular smooth muscle cells (VSMC) (27). The same study also demonstrated that CAT activity in VSMC was inhibited by Hcy, which is consistent with the results of our research.…”
Section: Discussionsupporting
confidence: 91%
“…To assess whether compound 1 could induce any morphological changes, HepG2 cells were incubated with different concentrations of compound 1 . The cells were then observed and photographed using a fluorescence microscope after being stained with 3,3′-dioctadecyloxacarbocyanine perchlorate (Dio) and Hoechst 33342 [ 12 , 13 ]. As shown in Figure 4 A, compound 1 altered the cellular morphology considerably regardless of the dose.…”
Section: Resultsmentioning
confidence: 99%
“…With the presence of U0126, an inhibitor of MEK1/2, the cultured neural progenitors were decreased after OGD compared with the one without U0126. In the research of Chang et al ( 2017 ), the neurite outgrowth was promoted by ARDD-activated ERK phosphorylation, which could be reversed by PD98059, an inhibitor of the ERK pathway. In Sun et al’s ( 2017 ) research, the neuronal apoptosis was significantly affected by NGF/HO-1-activated MEK/ERK pathway after the cultured primary cortical neurons were exposed to OGD.…”
Section: Discussionmentioning
confidence: 99%